Inquiry learning model with advance organizers to improve students' understanding on physics concepts. (April 2020) - Nisyah, M; Gunawan, G; Harjono, A; Kusdiastuti, M
Abstract: The inquiry model is one of the learning models that have the potential to train students' high-level skills and thinking. These activities require good initial knowledge of students. An advance organizer is one strategy that can be used to overcome this problem. The purpose of this study was to examine the effectiveness of the inquiry model with advanced organizers in improving students' conceptual understanding. The research design used was a non-equivalent pretest and posttest group. The research subjects were divided into two groups, namely the experimental group and the control group. Data were analyzed by N-gain test. The results showed that the understanding of the concept of the experimental group was better than the control group. Thus it can be concluded that the inquiry model combined with an advanced organizer is effective in increasing mastery of students' physics concepts. In general, the increase in the experimental group was higher than the control group both in the cognitive aspects and in each sub-material.